(untitled) (Eurasian Journal of Engineering and Technology, 2022)
Today, we will give information about the world’s electric vehicle industry through our article on the stages of development of the electric vehicle industry through the data we know and do not know, and statistical figures. In the future, we hope to apply the results of these data and studies to the electric car industry of Uzbekistan.